Statius and Virgil : the Thebaid and the reinterpretation of the Aeneid - Ganiban, Randall Toth, 1966- (Cambridge University Press, 2007)
Explores the degree to which Statius' Thebaid is engaged in a dialogue with the ideas and poetry of Virgil's Aeneid.